2003
DOI: 10.1023/b:brea.0000004373.09678.bb
|View full text |Cite
|
Sign up to set email alerts
|

Venezuelan Equine Encephalitis Replicon Immunization Overcomes Intrinsic Tolerance and Elicits Effective Anti-tumor Immunity to the ‘Self’ tumor-associated antigen, neu in a Rat Mammary Tumor Model

Abstract: SummaryMany tumor-associated antigens (TAAs) represent 'self' antigens and as such, are subject to the constraints of immunologic tolerance. There are significant barriers to eliciting anti-tumor immune responses of sufficient magnitude. We have taken advantage of a Venezuelan equine encephalitis-derived alphavirus replicon vector system with documented in vivo tropism for immune system dendritic cells. We have overcome the intrinsic tolerance to the 'self' TAA rat neu and elicited an effective anti-tumor immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 97 publications
(104 reference statements)
4
36
0
Order By: Relevance
“…Other advantages of VRP are their tropism for, and maturation of (5), DCs, which could result in enhanced T cell activation. A number of preclinical studies have reported that VRP induce potent immunity despite the presence of neutralizing antibodies (4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Other advantages of VRP are their tropism for, and maturation of (5), DCs, which could result in enhanced T cell activation. A number of preclinical studies have reported that VRP induce potent immunity despite the presence of neutralizing antibodies (4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…This class of virus is particularly attractive because the double-stranded RNA created during viral replication stimulates the innate immune response through interaction with TLR3 (23). Moreover, the efficacy of VRP vaccines based on VEEV has been attributed to the expression of heterologous proteins at high levels, to targeting expression to dendritic cells, and to the ability to induce both humoral and cellular immune responses against the product of the gene carried by the vector (24,26).…”
mentioning
confidence: 99%
“…The high degree of homology with other receptor tyrosine kinases, including other members of the HER family, and the expression of HER2/neu in normal tissues, pose significant challenges that need to be addressed, including overcoming the anticipated immunological tolerance while maintaining specificity of the elicited immune response. Much of the preclinical work was performed in HER2/neu transgenic mouse models due, in part, to the fact that a murine homolog was not confirmed until the early 2000s [14][15][16], although other models were also employed (dog, guinea pig, rat, primate) [209][210][211][212][213][214]. The majority of these have focused on the extracellular domain of HER2/neu due, in large part to the high degree of homology of the intracellular kinase domain with other receptor tyrosine kinases both in and outside of the HER family [209,[215][216][217][218][219], although some strategies have included elements from the intracellular domain [213][214][215].…”
Section: Her2/neu Antigen-specific Immunotherapymentioning
confidence: 99%
“…Dendritic cells (DCs) are the most potent antigen presenting and immune-stimulating cells within the immune system, thus, DC-based immunotherapeutic strategies directed against HER2/neu have been investigated, including DCs loaded with various fragments or peptides from the HER2/neu sequence [234][235][236][237] (NCT00266110 and NCT00923143) and transduced DCs [213,[237][238][239][240][241][242][243] including adenoviral transduced autologous DCs expressing the extra cellular and transmembrane domains of HER2/neu (NCT01730118). A preparation analogous to Sipuleucel-T (the first FDAapproved cellular based-immunotherapy) [244] is being developed, Lapuleucel-T, consisting of a HER2/neu truncated fusion with granulocyte macrophage colonystimulating factor that is used to generate an autologous mixture of antigen-presenting cells targeting the HER2/neu component [245].…”
Section: Her2/neu Antigen-specific Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation